The Effect of Self-Controlled and Instructor-Controlled Feedbacks on Acquisition, Retention and Transfer of a Motor Skill Using Videotape Feedback - Shida Ehsani; Elahe Arabameri; Ahmad Farokhi; Rasoul Zeydabadi (University of Tehran, 2009)
The purpose of the present study was to investigate the effect of self-controlled (SC) and instructor-controlled (IC) feedbacks on the acquisition of dart motor skill using videotape feedback. For this purpose, 200 female volunteer students of University of Tehran participated in this research. After the questioners had been filled out, 36 individuals were randomly selected from 152 qualified participants. After a 10-trial pretest, they were divided into three groups: SC, IC, and Yoked group. The SC group received videotape feedback whenever they asked for it; the IC group after 5 trails, and the yoked group at the points that SF group received it. All the groups were videotaped. Practice phase consisted of 100 trials including 10 10-trail blocks. Retention and transfer tests were carried out 48 hours later. Foe data analysis, one-way ANOVA, repeated measures and Tukey test were used and EXCEL software was used to draw the plots. The results showed that the type of feedback had a significant effect on the form and accuracy of dart motor skill in acquisition, retention and transfer (P